The Effect of Field Experience Program on Students' Teaching Skills: Study at Ibnu Chaldun University Jakarta - Fachrurrozy, Muhammad Syahdan; Kunaenih; Fahri, Muhammad Fadli (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to examine the influence of the Field Experience Program (PPL) on students' teaching skills. PPL is an integral part of the teacher education curriculum, which is designed to provide practical experience to students in real teaching situations. The research approach used in this study is a descriptive method with a quantitative approach. Data was collected through questionnaires that measured teaching skills before and after participating in PPL, as well as through direct observation during program implementation. The implication of this research is the need for higher education institutions to continue to develop and improve the quality of PPL programs to ensure that student teachers gain relevant and meaningful experience. This research concludes that PPL is an important component in teacher education, which can significantly improve students' teaching skills so that they are ready to face challenges in the real world of education.